De la necesidad a la preferencias: los significados de la libertad - Iguíñiz Echeverria, Javier María (2003)
In this paper we analyze the meaning of four concepts, subsistence, needs, wants and preferences from the viewpoint of their association with the concepts of life sustenance and freedom. Our aim is to show that the concentration by mainstream economic theory in the last two allows it to avoid dealing with the most important economic problems of today: poverty and underdevelopment. Moreover, it trivializes the meaning of freedom, and specifically of freedom to choose. As freedom increases, loses substance.